The Application of Selected Broadband Red Filters for Red-Green Deficiencies - Egan, Donald J (Canadian Journal of Optometry, 1982)
This paper will review some of the various coloured filters used to aid chromatic discrimination for the red-green deficient. These range from hand-held rapid comparison devices, the so-called 'quick-specs', to daily-wear daytime spectacles or contact lenses. Also included are a consideration of published reports, some preliminary observations with sample populations, and a discussion of the spectral transmission of selected materials as determined with the Zeiss DMR 21 Spectrophotometer.